Qualitative description of the prevalence and use of anabolic androgenic steroids by United States powerlifters - Curry, L. A.; Wagman, D. F. (Perceptual and Motor Skills, 1999)
Powerlifters have been suspected to be a population wherein use of anabolic androgenic steroids is prevalent (Yesalis, Herrick, & Buckley, 1988). To access commentary from these athletes on issues related to these drugs and the effectiveness of doping controls, a survey was developed. From 28 U.S. Powerlifting Team members who competed internationally since 1988, 26 were contacted by mail, and 15 questionnaires were returned. The questionnaire solicited yes/no responses and qualitative descriptions about current and previous use of anabolic androgenic steroids in powerlifting. Analysis indicated that ten U.S. Powerlifting Team members admitted to using these drugs, and five athletes admitted to beating the International Olympic Committee's doping control procedures. Reported use of anabolic androgenic steroids by these athletes was consistent with data presented by Yesalis, et al. and illustrated continued discrepancy between admitted use of these drugs prior to or during national and international events and the lack of reported positive test data. Discussion focused on the value of this study to elicit in an athlete's own words commentary specific to the use of anabolic androgenic steroids and the need for more effective doping controls.